Penanaman Nilai Karakter Melalui Lagu Dolanan Anak dalam Pembelajaran Daring Di SD Negeri 01 Mejagong - Felina Ela Wijiasih; Khusnul Fajriyah; Sukamto Sukamto (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
The background in this research is the rapid development of the times so that character building in the current era of modernization is very much needed so that the national identity and indigenous culture of Indonesia are not eroded by modernization because we are faced with developments in various fields such as politics, economy, science and technology and socio-culture. The objective of this research is to find out what character values ​​are contained in children's prayer songs and how to instill character values ​​through children's kids songs in online learning. This research was conducted at SD Negeri 01 Mejagong class III, amounting to 26 students using observation, interview and questionnaire techniques. Based on the research findings, the character values ​​contained in the song lyrics of kids songs ilir-ilir, Padhang Bulan and Menthok-menthok are religious, nationalist, integrity, and independent character values. Meanwhile, the inculcation of character values ​​through the kids songs taught by the teacher during online learning is carried out by habituating the behavior of students in accordance with the meaning of the kids songs so that the character values ​​in students can be seen during online learning.